ACTIVITY PATTERNS OF JAGUAR, PUMA AND THEIR POTENTIAL PREY IN SAN LUIS POTOSI, MEXICO - Hernández-SaintMartín, Anuar D.; Rosas-Rosas, Octavio C.; Palacio-Núñez, Jorge; Tarango-Arámbula, Luis A.; Clemente-Sánchez, Fernando; Hoogesteijn, Almira L. (Instituto de Ecología, A.C., 2013)
Jaguars (Panthera onca) and pumas (Puma concolor) are sympatric species in Mexico and have ecological similarities. The understanding of interespecific interactions between these species are important for effective conservation strategies. We studied activity patterns of jaguars, pumas and their potential prey species through camera-trapping photographs obtained by during four seasonsin the Abra-Tanchipa Biosphere Reserve , San Luis Potosí, Mexico. We described activity patterns of 12 terrestrial vertebrate species, the degree of overlap of jaguar and puma activity; and the prey – predator relationship. Both felids showed cathemeral activity and overlapping between their activities. Jaguar activity showed a significant correlation with eight prey species activity. Puma activity was no related with any prey species activity. Activity peaks of both felids suggest that temporal segregation is a strategy which minimizes interspecific encounters allowing the coexistence of several individuals in this small reserve.